Elaboration of project work plan - Гладка, Мирослава Вікторівна; Хлобистова, Ольга Андріївна (Eastern-European Journal of Enterprise Technologies, 2013)
The article justifies the necessity of the elaboration of project work plan in the course of automation of an organization. The approaches used in the development of project plans were considered. The necessity of the situational approach when elaborating a plan for the implementation of information system was proved. The main elements of the project that affect the quality of its implementation were singled out. The application of the method PERT, when planning the terms of the project, and Gantt charts, when constructing sequence graph of work performance, was explained. Methods of improvement of the plan of project works and resource management at all stages of enterprise automation were considered. During the planning of the project, attention was focused on the development of schedule, where the works performed on a scale of one implementation conform over time with the possibility of their provision with different kinds of logistical and labour resources. When planning the use of resources for the project it is necessary to take into account that the construction of the project structure provides forecasting of expenditures for each of the works with specification of restrictions in the form of general (common) plans. The resource planning of the lower stage is the initiation of amendments and adjustments to the overall plan. It was proved that the use of the plan had positive effect on the outcome of implementation